Thinking Inside The Box: Future Of Sequential Interplay Of Art And Words - Anupama. R (International Journal of Advanced Science and Technology, 2020)
Graphic Novels are hard to be defined as a mere sequential art. Evolved from comics, they are narratives comprising of fiction and nonfiction covering myriad genres, interdependent on words and images. Over the past 30 years, this narrative medium has transcended from being called “Alternative Comix” to permeate into contemporary mainstream literature, progressing to even make it into the long list of the Man Booker prize. This paper attempts to trace the promising future of the Graphic Novels by exploring its efficiency to illustrate complex concepts of urban life, societal stigmas, historical events, biographical/autobiographical elements and traumatic experiences across genres, across cultural and geographical borders beyond words.